Detik.com and Tempo.co in Framing the Persecution of Papuan Citizen by TNI - Tarigan, Inggit Yulis Sutari; Mulyani, Henny Sri; Aunillah, Rinda (Universitas 17 Agustus 1945 Surabaya, 2025)
A video depicting a Papuan citizen, Definus Kogoya, being brutally beaten by members of the Indonesian National Armed Forces inside a water drum went viral on the social media platform X on March 22, 2024. This incident quickly attracted widespread public attention and became a major topic of discussion in Indonesia. Among the various media outlets covering the issue, Detik and Tempo emerged as the most prominent, publishing a combined total of 41 news reports. The objective of this research is to analyze the messages conveyed through the framing of news coverage by these two media organizations. The study employs the framing analysis approach developed by Gamson and Modigliani, which focuses on how media select and present news stories, including the choice of words, images, and the overall focus of reporting. A qualitative approach is utilized to enable a more comprehensive and in-depth exploration of the issue. Gamson and Modigliani’s framework distinguishes between framing devices—such as metaphors, catchphrases, exemplars, depictions, and visual images—and reasoning devices, which include identifying root causes, appeals to principle, and highlighting consequences. Primary data for this research were collected from online news articles, while secondary data were sourced from relevant books and academic journals. The research sample consists of 13 news reports, with 6 articles from Detik.com and 7 from Tempo.co. The findings reveal significant differences in how the two media outlets frame the incident. Detik.com tends to present the persecution of Definus Kogoya as an event triggered by allegations of arson at a local health center, focusing on the immediate context of the incident. In contrast, Tempo.co frames the event as part of a longstanding, deep-rooted conflict in Papua, attributing the violence to the government’s failure to take decisive action in resolving the broader conflict. These findings highlight how media framing can shape public understanding of sensitive issues and underscore the importance of critical analysis in interpreting news coverage within a wider socio-political context. Keywords: Definus Kogoya, Framing, Gamson and Modigliani, Detik.com, Tempo.co.